Relato de um paciente brasileiro com síndrome de Wolfram Report of a Brazilian patient with Wolfram syndrome - Paulo R.G. Zen; Louise L.C. Pinto; Ida V.D. Schwartz; Timothy G. Barrett; Giorgio Paskulin (Elsevier, 2002)
Objetivos: relatar o caso de um paciente com diagnóstico de síndrome de Wolfram (SW) e braquidactilia do tipo E. A síndrome de Wolfram é caracterizada pela presença de diabetes melito, diabetes insípido, atrofia do nervo óptico, alterações do trato urinário, surdez e distúrbios neurológicos e psiquiátricos. No entanto, nem todas as manifestações estarão presentes no momento do diagnóstico, indicando a necessidade de acompanhamento a longo prazo destes pacientes. Este acompanhamento deve ser estendido aos familiares diretos, tendo em vista o risco aumentado da ocorrência de distúrbios psiquiátricos e diabetes melito entre os portadores heterozigotos da síndrome de Wolfram. Descrição: menino, branco, filho de pais não consangüíneos, era hígido até os 4 anos, quando iniciou com polidipsia e poliúria, sendo diagnosticada diabetes melito tipo I. Desde então, faz uso irregular de insulina e segue mal a dieta por problemas socioeconômicos. Foi avaliado pelo serviço de Genética aos 11 anos de idade. Ao exame físico, chamou a atenção a presença de braquidactilia. Durante a investigação complementar, constatou-se atrofia bilateral do nervo óptico, com potencial evocado visual e eletrorretinograma compatíveis com lesão grave de nervo. Ambas retinas eram normais. A presença de diabetes melito insulino-dependente e atrofia do nervo óptico são critérios suficientes para o diagnóstico de síndrome de Wolfram. A investigação molecular confirmou o diagnóstico. Comentários: o presente relato tem o objetivo de alertar os profissionais da área médica para a associação entre o diabetes melito e síndromes monogênicas, como a SW. ABSTRACT Objective: to report a case of a patient diagnosed with Wolfram Syndrome and brachydactyly type E. Wolfram Syndrome is characterized by the presence of diabetes mellitus, diabetes insipidus, atrophy of the optic nerve, alterations of the urinary tract, deafness and neurologic and psychiatric disorders. However, not all manifestations are present at diagnosis, indicating the necessity of long-term follow-up of these patients. This long-term follow-up should be extended to the patients' closest relatives, having in mind the increased risk of occurrence of psychiatric disorders and diabetes mellitus among the heterozygous carriers of Wolfram Syndrome. Description: male, white patients, only child of non-consanguineous parents, was healthy until four years of age, when he presented with polydipsia and polyuria, being diagnosed with diabetes mellitus type I. Since then, he has needed regular insulin use, but has followed an inadequate diet due to socioeconomic problems. He was evaluated by the genetic service when he was 11 years old. Brachydactyly was observed on physical examination. In the course of the complementary investigation, bilateral atrophy of the optic nerve was observed; the visual evoked potential and the electroretinogram were compatible with extensive optic nerve injury. Both retinas were normal. The presence of insulin-dependent diabetes mellitus together with atrophy of the optic nerve is a sufficient criterion for the diagnosis of Wolfram Syndrome. The molecular investigation confirmed the diagnosis of Wolfram Syndrome. Comments: the aim of the present report is to alert physicians about the association between diabetes mellitus and monogenic syndromes, such as Wolfram Syndrome.